Pet Tracking System Using Telegram Notification - Daeng Dwi Prasojo; Shazana Dhiya Ayuni; Izza Anshory; Arief Wisaksono (Universitas Nurul Jadid, 2026)
This research aims to design and implement a pet tracking system using GPS Neo-6M and LoRa SX1278 modules with Telegram integration for real-time location monitoring. The system consists of a transmitter unit using Arduino Nano, a GPS module, and a LoRa module to send coordinates. The receiver uses a LoRa module and an ESP8266 microcontroller connected to the internet, which forwards the GPS data to a Telegram bot. The test results show that the system successfully sends accurate location data from the pet’s location to the owner via Telegram. This system is suitable for areas with limited internet coverage, offering low power consumption and long-range communication. It enhances the safety of pets through real-time monitoring and is highly applicable in various outdoor scenarios